Evolution and Phylogeny of Large DNA Viruses, Mimiviridae and Phycodnaviridae Including Newly Characterized Heterosigma akashiwo Virus - Maruyama, Fumito; Ueki, Shoko (Frontiers in Microbiology, 2016)
Nucleocytoplasmic DNA viruses are a large group of viruses that harbor double-stranded DNA genomes with sizes of several hundred kbp, challenging the traditional concept of viruses as small, simple ‘organisms at the edge of life’. The most intriguing questions about them may be their origin and evolution, which have yielded the variety we see today. Specifically, the phyletic relationship between two giant dsDNA virus families that are presumed to be close, Mimiviridae, which infect Acanthamoeba, and Phycodnaviridae, which infect algae, is still obscure and needs to be clarified by in-depth analysis. Here, we studied Mimiviridae–Phycodnaviridae phylogeny including the newly identified Heterosigma akashiwo virus strain HaV53. Gene-to-gene comparison of HaV53 with other giant dsDNA viruses showed that only a small proportion of HaV53 genes show similarities with the others, revealing its uniqueness among Phycodnaviridae. Phylogenetic/genomic analysis of Phycodnaviridae including HaV53 revealed that the family can be classified into four distinctive subfamilies, namely, Megaviridae (Mimivirus-like), Chlorovirus-type, and Coccolitho/Phaeovirus-type groups, and HaV53 independent of the other three groups. Several orthologs found in specific subfamilies while absent from the others were identified, providing potential family marker genes. Finally, reconstruction of the evolutionary history of Phycodnaviridae and Mimiviridae revealed that these viruses are descended from a common ancestor with a small set of genes and reached their current diversity by differentially acquiring gene sets during the course of evolution. Our study illustrates the phylogeny and evolution of Mimiviridae–Phycodnaviridae and proposes classifications that better represent phyletic relationships among the family members.